Síntese de nanopartículas de sulfeto de cobre, preparação e estabilidade coloidal de fluidos trocadores de calor em meio aquoso - Santos, Caio Carvalho dos [UNESP] (2015)
The search for new materials with improved physical and chemical properties has intensified in recent years due to advances in nanotechnology. These advances have allowed the miniaturization and increased performance of various systems and devices. In this context has intensified the search for ways to increase the thermal conductivity (k) heat exchanger systems, through nanofluids employment, involving the dispersion of nanomaterials in a traditional fluid heat exchanger (water, ethylene glycol and oils). This dispersion is designed to enable a large increase in heat transfer rate of heat exchangers devices. Nanofluids must be stable for long periods of time, so it should try to inhibit the aggregation trends of these nanomaterials, through the use of protective strategies and stabilization of nanoparticles that comprise it. The use of such dispersion stabilization strategies are correlated to study the stability of colloidal systems. In this paper, nanofluids containing stable aqueous copper sulfide nanoparticles for long periods were obtained. The aqueous fluid is advantageous due to its higher thermal conductivity between traditional fluids, in addition to its low toxicity compared to body fluids. Obtaining copper nanoparticles in aqueous medium is a challenge to the stability of the colloidal dispersion formed due to oxidation of metallic nanoparticles. Various surfactants were tested to prepare stable aqueous nanofluids. The nanofluid with high chemical stability and was colloidal produced with thioglycolic acid as surfactant. The presence of mercapto group in this reaction led to the formation of copper sulfide nanoparticles with colloidal stability more than 389 days. The particles were characterized for morphology and size distribution by transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The colloidal stability of nanofluids was assessed by zeta potential...